Can microlearning strategy assist students’ online learning? - Rudi Susilana; Laksmi Dewi; Gema Rullyana; Angga Hadiapurwa; Nanda Khaerunnisa (LPMPP Universitas Negeri Yogyakarta, 2022)
The development of information and communication technology leads to the need for learning concepts and strategies following current conditions. In the higher education system, it is essential that educators must carefully consider the learning strategies of students' learning styles and cognitive loads. This study explores how microlearning strategies are applied to online learning to minimize students' cognitive load. It applies a qualitative approach by involving 45 students in the student mobility program who volunteered to participate in the research process. The data were collected through questionnaires, interviews, and document analysis of student learning outcomes. They were then validated by triangulation and analyzed by following an interactive data analysis model on applying microlearning strategies in online learning. The results showed that microlearning is an effective strategy to minimize students' cognitive load in online learning, including intrinsic, extraneous, and germane ones. The implementation of microlearning strategies in online learning eases students to understand the material; students are more flexible in learning because its strategy allows students to decide their readiness to learn. This strategy enables students to manage the unproductive cognitive load and stimulate the germane cognitive load. Hence, their learning outcomes fall into the nearly excellent category.